Adolescentes com diabetes Mellitus tipo 1 :seu cotidiano e enfrentamento da doença - Santos, Jocimara Ribeiro dos (2001)
The adolescence period has been studied under different approaches, and there are divergences about its universality. It is known, however that the physical transformations of puberty also cause psychosocial changes. This redefinition of roles, thoughts and attitudes can be quite influenced by the existence of a chronic disease as Diabetes Mellitus Type 1, which has the incidence of 1 or 2 in each hundred adolescents. They may have their daily routine altered. With the aim to describe and analyze how Diabetes Mellitus Type 1 affect adolescents’ coping and organize their daily routines, a comparison was made between adolescents with and without the disease. This research was undertaken with 15 adolescents (6 male and 9 female, with their age ranging from 12 to 20 years) enrolled in the Vitória’s public health Diabetes Mellitus Bearers Attendance Programs. The subjects were submitted to the collective and individual application of Daily Activities Map (DAM), (Menandro, Menandro & Oliveira, 1999) and to a closed/open individual interview, about coping. The DAM was applied collectively to 224 young adolescents without disease (122 girls and 102 boys, their age ranging from 12 to 20 years), students from Medium and Fundamental levels, from public schools in greater Vitória/ ES, for a comparative comparison. The data obtained from DAM were analysed through quantitatively and qualitatively analyzed, intending a differentiated evaluation of the author’s proposal; the interviews were content analysis. The data revealed that activities more accomplished by the adolescents were: activities directed to themselves, activities inside their home, pleasant ones, social ones, and that it involved action and control to alcohol consume. The activities more accomplished inside the house were: attending television programs and listening to some music. Despite the joet that Diabetes Mellitus Type 1 affected adolescents, pointing some difficulties in relation to the disease, they didn’t have their routine modified because of the disease. The results indicated that the adolescents with diabetes do not differentiate, in a significant way, from those without the disease.